Exploration of DNA processing features unravels novel properties of ICE conjugation in Gram-positive bacteria. Issue 14 (18th July 2022) - Laroussi, Haifa; Aoudache, Yanis; Robert, Emilie; Libante, Virginie; Thiriet, Louise; Mias-Lucquin, Dominique; Douzi, Badreddine; Roussel, Yvonne; Chauvot de Beauchêne, Isaure; Soler, Nicolas; Leblond-Bourget, Nathalie
Abstract: Integrative and conjugative elements (ICEs) are important drivers of horizontal gene transfer in prokaryotes. They are responsible for antimicrobial resistance spread, a major current health concern. ICEs are initially processed by relaxases that recognize the binding site of oriT sequence and nick at a conserved nic site. The ICE St3 /Tn 916 /ICE Bs1 superfamily, which is widespread among Firmicutes, encodes uncanonical relaxases belonging to a recently identified family called MOBT . This family is related to the rolling circle replication initiators of the Rep_trans family. The nic site of these MOBT relaxases is conserved but their DNA binding site is still unknown. Here, we identified the bind site of RelSt3, the MOBT relaxase from ICE St3 . Unexpectedly, we found this bind site distantly located from the nic site. We revealed that the binding of the RelSt3 N-terminal HTH domain is required for efficient nicking activity. We also deciphered the role of RelSt3 in the initial and final stages of DNA processing during conjugation. Especially, we demonstrated a strand transfer activity, and the formation of covalent DNA-relaxase intermediate for a MOBT relaxase.